2022
DOI: 10.3390/foods11050748
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Pepper Seed By-Products: A Review

Abstract: Peppers are grown all around the world, usually for fresh consumption, as well as for the industrial production of different products. Pepper (Capsicum annuum L.) seeds are mostly considered a by-product. Recent investigations have shown that pepper seeds have the potential to be a valuable source of edible oil and fiber-rich flour and protein after processing. Pepper seed oil is a high-quality edible oil according to quality analysis (nutritional, chemical, sensory and antioxidant characteristics) and is suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
(128 reference statements)
1
10
0
Order By: Relevance
“…The inclusion of seeds in the chili powder reduces total phenolic content [ 64 ] but has a preserving effect on color compounds due to the presence of tocopherols [ 51 ]. Tocopherols are lipophilic molecules concentrated in the oil-rich parts of the seeds [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of seeds in the chili powder reduces total phenolic content [ 64 ] but has a preserving effect on color compounds due to the presence of tocopherols [ 51 ]. Tocopherols are lipophilic molecules concentrated in the oil-rich parts of the seeds [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, HPOB could potentially be used as a fat replacer and an antioxidant agent when producing a low-fat emulsion. In addition, it has been revealed that HPOB has antibacterial, antioxidant [ 13 ], and anti-corrosive characteristics [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, more than half of the raw material from the orange juice industry are wasted, which means the loss of a good source of dietary fibre, phenolic compounds, and minerals 75 , 76 . Likewise, pepper and tomato by-products are also considered good sources of dietary fibre, phenolic compounds, proteins, carbohydrates, and lipids 77 , 78 . Likewise, Table 1 shows that apple by-products had the highest concentration of total carbohydrates and sugars, followed by orange, green pepper, and tomato.…”
Section: Discussionmentioning
confidence: 99%